(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The current research aims to identify the role of integration of money exchange companies in enhancing the role of supervision of the Central Bank of Iraq, where the importance of the research lies in shedding light on the consequences of the existence of a large number of money exchange companies in an unorganized economic sector in Iraq and highlighting the importance of directing these economic entities to merge in order to reduce their number on the one hand and raise their level of organization on the other hand, while the problem of the research is that the integration of money exchange companies in Iraq is a significant problem in enhancing the role of supervision of the Central Bank of Iraq. Integration is considered one of the most important steps that can be taken to enhance supervision of the money exchange sector and improve its financial performance, and the researcher has reached a number of conclusions and recommendations, including that integration processes are one of the strategic options that companies take to overcome the difficulties and problems they face in various fields, the need to prepare comprehensive economic and technical feasibility studies by relevant government agencies to expand the integration of companies in order to achieve competitiveness advantages for the Iraqi economy and environment in light of current conditions and achieve the best use of available resources, the need to disclose the method or process of integration and its implications for the Iraqi economy and the banking sector in general, and the importance of considering the social and economic impacts of integration on the various segments of society.